Let f(x)=3x-1 and g(x)=x^2+4 find (f g)(-2) May 7 | Theresa from Milltown, NJ | 1 Answer | 0 Votes Mark favorite Subscribe Comment Comments Is it (f+g)(-2), (f-g)(-2) or (f o g)(-2)? May 7 | Philip P. (f o g)(-2) May 7 | Theresa from Milltown, NJ Comment
f(x ) = 3X -1 g( x ) = X^2 +4 ( f +g) ( -2 )= [( 3(-2) -1 +(-2^2) + 4] = = ( -6 - 1 +4 +4 ) = 1 ( f - g ) ( -2) = [ 3(-2) -1 - ( -2^2 +4 ) ]= = ( -7 -8) = -15 (f ° g ) (-2 ) = [ 3 (-2^2 + 4) - 1 ] = = 3( 8) - 1 = 23 May 7 | Parviz F. Comment
Comments